Static analysis of deep-water marine riser - Syeh Muhammad Hafiz Sahrum (2014)
This paper explores the static configuration of deep-water marine riser via mathematical formulation of catenary equations. The ordinary differential catenary equations were derived for small and large deformations. Focus was placed more onto the large deformation catenary equations as in the application of deep-water marine riser, Top-Tensioned risers (TTR) are astronomically more costly than Steel Catenary Risers (SCR). The ordinary differential catenary equations were simplified. From the simplification of the equations, standard catenary solutions were conceived proving that the initial derivations were valid. The catenary equations were then analysed using various mathematical software like Mathematica and Excel Solver. These software enable the parametric study of the catenary equations by varying various parameters like horizontal tension (H), weight per unit length (w) and the catenary length (s). After analysing the equations with no external force acting on it, external constant force was considered into the analysis. Thereafter, a simplified parabolic force was considered to model an actual riser. After gaining an understanding of the previous analysis, a scenario of varying the horizontal distance of the vessel and maintaining the depth of sea was considered. This is done because in reality the vessel will surge and sway.